2013
DOI: 10.1080/01690965.2013.805795
|View full text |Cite
|
Sign up to set email alerts
|

Prosody and information structure in a tone language: an investigation of Mandarin Chinese

Abstract: Prosody conveys discourse-level information, but the extent to which prosodic cues distinguish different kinds of information-structural concepts remains unclear. The prosodic encoding of information structure is even more complicated in tone languages, where acoustic cues such as FO, intensity and duration also distinguish lexical items (e.g. Mandarin). Prior work on Mandarin led to divergent findings regarding whether and what prosodic cues mark the distinctions between information-structural types. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 32 publications
7
24
0
Order By: Relevance
“…The present results provide data that converge with results from scene description and event description tasks (e.g., Kahn & Arnold, 2012, in press; Lam & Watson, 2010, 2014; Ouyang & Kaiser, in press; Vajrabhaya & Kapatsinski, 2011) in suggesting that prosodic prominence is influenced by the ease of retrieving the representations required for language production—and that different acoustic correlates of prominence may be influenced by different variables. One potential concern with conclusions from those tasks is that some (though not all) of the tasks, especially those purporting to demonstrate multiple sources of prosodic prominence, involved experimental manipulations that disrupted the natural correlations between variables.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present results provide data that converge with results from scene description and event description tasks (e.g., Kahn & Arnold, 2012, in press; Lam & Watson, 2010, 2014; Ouyang & Kaiser, in press; Vajrabhaya & Kapatsinski, 2011) in suggesting that prosodic prominence is influenced by the ease of retrieving the representations required for language production—and that different acoustic correlates of prominence may be influenced by different variables. One potential concern with conclusions from those tasks is that some (though not all) of the tasks, especially those purporting to demonstrate multiple sources of prosodic prominence, involved experimental manipulations that disrupted the natural correlations between variables.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, several studies have found that duration and intensity show different influences and do so in ways consistent with the present data. Several experiments (Lam & Watson, 2010, 2014; Ouyang & Kaiser, in press) have found reduction in duration stems mostly from lexical repetition; reduction of duration effects has thus been attributed (Bard et al, 2009; Lam & Watson, 2014) to implicit activation of lexical forms. However, such implicit memory effects rarely transfer across modalities or to free recall (Roediger, 1990), a task that primarily probes participants’ knowledge of what referents were discussed in the discourse rather than their ability to quickly produce lexical forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experimental evidence has revealed different acoustic correlates of focus in different contexts. For instance, Ouyang and Kaiser [10] found that Mandarin words produced with corrective focus had longer durations, greater pitch expansion, and larger intensity ranges, while words that indicated new information only showed duration lengthening and pitch expansion. Similarly, in English, speakers are more likely to produce rising (L+H*) accents to encode elements in the discourse that signal explicit contrastive information [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the prosodic marking of focus in Chinese has mostly emphasized the phonetic prominence of a single focused disyllabic word of Tone 1 (the high-level tone) serving as the subject or object in a Mandarin sentence, but different findings were reported. For example, narrow wh-focus may involve longer duration [4], larger f o ranges [4] [5], or higher mean f o [6], and it is reported that correction is distinguished from old information by longer duration, higher intensity, and larger f o range [7]. It remains unclear (a) whether different types of foci (e.g., information focus vs. corrective focus) are prosodically expressed differently, and (b) whether focus representations are acoustically distinguishable from the underlying lexical tones.…”
Section: Introductionmentioning
confidence: 99%